2005
DOI: 10.1007/s10812-005-0146-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Solvent on the Quantum Yield and Duration of the Fluorescence of Tetraazoporphin

Abstract: ev UDC 535.37In view of the discrepancies between the values available in the literature for the photophysical parameters of tetraazaporphin in solutions, we measured its quantum yield and duration of fluorescence in a number of solvents. It has been found that alcohols (isobutanol and isopropanol) quench the fluorescence appreciably. For a solution in toluene -a stable chemically inactive and low-polar solvent -the measured quantum yield of the fluorescence of tetraazaporphin is equal to 0.180 ± 0.015 and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The same effect is found for related aza-BODIPY dyes and with other hydrogen-bond donors, including water, and counts against using aza-BODIPY dyes as sensitizers in aqueous media. It might be noted that a similar effect was reported earlier for aza-porphyrins, where it was observed that isobutanol shortened the excited singlet state lifetime to 1.5 ns compared to a value of 3.4 ns found in toluene, and was explained in a similar manner. Interestingly, ethanol has only a marginal effect on the excited singlet state lifetime of a highly constrained analogue of aza-BODIPY, where attachment to the meso -aza N atom is partially blocked by aryl substituents at the 1,7-positions.…”
Section: Resultssupporting
confidence: 84%
“…The same effect is found for related aza-BODIPY dyes and with other hydrogen-bond donors, including water, and counts against using aza-BODIPY dyes as sensitizers in aqueous media. It might be noted that a similar effect was reported earlier for aza-porphyrins, where it was observed that isobutanol shortened the excited singlet state lifetime to 1.5 ns compared to a value of 3.4 ns found in toluene, and was explained in a similar manner. Interestingly, ethanol has only a marginal effect on the excited singlet state lifetime of a highly constrained analogue of aza-BODIPY, where attachment to the meso -aza N atom is partially blocked by aryl substituents at the 1,7-positions.…”
Section: Resultssupporting
confidence: 84%
“…(Only the τ F value was reported in our earlier detailed publica tion [10].) Because of the discrepancies taking place in the literature concerning ϕ F data for H 2 TAP, we mea sured (with tetraphenylporphine in toluene as the standard) and for an H 2 TAP solution in toluene (ϕ F = 0.18, τ F = 3.4 ns) and in some other solvents [24]. These measurements are in satisfactory agree ment with earlier reported data ( Table 1).…”
Section: Photophysical Characteristicsmentioning
confidence: 99%
“…Quantum yields of fluorescence (ϕ F ) and singlet oxygen of luminescence (ϕ ∆ ) at room temperature were determined by the relative method with toluene solutions of tetraazaporphin (ϕ F = 0.18) [28] and Pt-dibenzo-tetraaza-iso-bacteriochlorin (ϕ ∆ = 0.72) [29] as standards, respectively. The phosphorescence quantum yields ϕ P at 77 K were calculated relative to the fluorescence quantum yield ϕ F using the ratio of the areas under the fluorescence and phosphorescence spectral curves.…”
Section: Photophysical Measurementsmentioning
confidence: 99%